La protección, agilidad y oportunidad, para la designación de curador dentro de la ley notarial. - GARCÍA CALLE, EDITH ALICIA (2013)
The notary law, born as a source of private law, to establish the mechanisms of "public faith", insofar as different acts of will and consciousness within the legislation, which are vented several legal acts for the benefit of society, as a source of the actions of persons in its various activities. Interdiction and curatorship of goods, are legal institutions, requiring an agile and timely treatment under its social significance, requiring special legal analysis, in order to grant the authority to the formality of this action to notaries public, in virtue of being officials envestida of public faith. The current reality, within the scope - legal partner in which the human being develops, is necessary that legal institutions are agile and timely as the purpose that plays its protective role of legal goods, through the status quo, through legal regulations; by how much constitutes a fundamental part of the guarantees, equity and security. The individual as being social, maintains the freedom of discernment, conscience and desire, budgets that are embodied in the legal capacity to act and be bound. Legal capacity considered as the faculty that people have to act and declare their will as well have to theirs, without violating the rights of others and the law, is the content of the reason to formulate actions of their development in the society. The relevance of the present legal research work, is closely related, the theoretical content and developed field research, furthermore is necessary indicate that it contains feasible budgets, which allowed me to meet with punctuality, the contribution of the verification of the proposed objectives and the rationale of the proposal, with the apparent support of bibliography according to the topic discussedwho helped raise the changes that I allowed me to formulate, as a major source of a neat analysis. Scientific research, is also presented as a source of inquiry and pursuing intellectual and coherent, where are born postulates methodological character and systematic teaching, which is interpreted within it, on the feasibility of incorporating into law attorney, regulations that allow the authorities of "Public faith", arrive at actions notarial legal of the wardshipinstitutionin the case of the injunctions declared in his notarial intervention with respect to the drunken customary and drug addicts, among others, the insane, and deaf-mute heatsinks. Literary references that summarize the conceptual aspect of trends and more timely postulates of Notarial Law, part of the civil law as the primary source of social actions, and teaching in terms of the legal research methodological references whose parameters were determined the success of this work.